COGNITIVE CHANGES IN DISTANCE LEARNING IN THE DIGITAL AGE: DEVELOPMENT OF INFORMATION SKILLS OR MEMORY OUTSOURCING? - Fatima Zohra BENAÏCHA (Universitaria Publishing House, Craiova, 2021)
In the context of the health crisis, we observe a growing interest in the use of technological mediation tool and collaborative remote work space (Giraud & Ranucci, 2003). This form of learning how to process digital information remains a new device for the co-construction of knowledge and even for the development of "collective intelligence" (Levy, 2006). Indeed, the systematic integration of ICT and the formalization of exchanges via platforms, such as Moodle, places users in front of issues linked to the asynchronous mediated coexistence and the transformation of learning and teaching models and therefore a new mode of memory outsourcing (Chang, Tijus & Zibetti, 2015). These upheavals in the university path in the digital age place, in part, the emphasis on the cognitive dimension of digital tools and the importance of an informational competence thus allowing the student to develop effective practices in "literacy. Digital" (Lankshear & Knobel, 2011). In other words, the individual must be able to understand, evaluate and properly reuse the information sent online by the teacher. Remote information literacy is a social act that promotes student interaction, autonomy and cognitive development. He thus becomes an active agent during his scientific/intellectual training and responsible for the process of (re) construction of knowledge according to the needs of the digital society (Legros, Benaïcha, Ben Ismail, & Sawadogo, 2008).